Designing sustainable online support: Examining the effects of design change in 49 online health support communities. (17th May 2019) - Introne, Joshua; Erickson, Ingrid; Semaan, Bryan; Goggins, Sean
Abstract : Online social support communities can significantly improve health outcomes for individuals living with disease. Although they are well studied in the literature, little research examines how sociotechnical design changes influence the sustainability of support communities for different medical conditions. We compare the impact of a single design change on 49 disease‐specific health support forums hosted on the WebMD platform, a popular online health information service. A statistical analysis showcases changes in posting patterns before and after the design intervention; a subsequent interpretive examination of forum content reveals how the design change affected members' perceived affordances of the platform. Our findings suggest that, despite differences between communities, the design change triggered a common set of cascading effects: it made it difficult for core users to create and maintain relationships, that led them to ultimately leave the site, and, in turn, reduced the activity drawing newcomers to the platform. Using these findings, we argue that the design of sustainable and robust online communities must account for systemic, sociotechnical dynamics.